2a+3b+4c=9abc

Simple and best practice solution for 2a+3b+4c=9abc equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+3b+4c=9abc equation:


Simplifying
2a + 3b + 4c = 9abc

Solving
2a + 3b + 4c = 9abc

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9abc' to each side of the equation.
2a + 3b + -9abc + 4c = 9abc + -9abc

Reorder the terms:
2a + -9abc + 3b + 4c = 9abc + -9abc

Combine like terms: 9abc + -9abc = 0
2a + -9abc + 3b + 4c = 0

Add '-3b' to each side of the equation.
2a + -9abc + 3b + -3b + 4c = 0 + -3b

Combine like terms: 3b + -3b = 0
2a + -9abc + 0 + 4c = 0 + -3b
2a + -9abc + 4c = 0 + -3b
Remove the zero:
2a + -9abc + 4c = -3b

Add '-4c' to each side of the equation.
2a + -9abc + 4c + -4c = -3b + -4c

Combine like terms: 4c + -4c = 0
2a + -9abc + 0 = -3b + -4c
2a + -9abc = -3b + -4c

Reorder the terms:
2a + -9abc + 3b + 4c = -3b + 3b + -4c + 4c

Combine like terms: -3b + 3b = 0
2a + -9abc + 3b + 4c = 0 + -4c + 4c
2a + -9abc + 3b + 4c = -4c + 4c

Combine like terms: -4c + 4c = 0
2a + -9abc + 3b + 4c = 0

The solution to this equation could not be determined.

See similar equations:

| 92-2x=10+20 | | -2p+10=-12p-20 | | B-5x=-3 | | 128-N=48 | | 3(k+2)-5(k-2)=-2k-4 | | -x^3-5x^2=6x | | 35.50=1.7n+1.5 | | -4+10q=10q-8 | | 3p+2=-4 | | (9x-6)3power=9 | | 128-N=46 | | 6x^2-400=0 | | y=3x^4-2x^3+74x^2-50x-25 | | 25x^2+1=37 | | 6x^2-400=9 | | 4e=36 | | 2/3*54 | | (9-6)3=9 | | 5/6x-5/6=5 | | 5(3-x)+2(3-x)=14 | | 3a+b-45=2a+4b-465.23+-a+507.23b | | 2x+8x-20=90 | | 15x+8=2x+2 | | -3x+4=-5x-9 | | 1/2m+3 | | 2.16+2=72 | | 6+2/3y=-12 | | 3x-(7x-4)=5x-(2x+10) | | z/17=-19 | | 14-3/4x | | 4-3x=5(x+4) | | 3a+b-45=2a+4b+465.23+-a+507.23b |

Equations solver categories